Optimalisasi Pemahaman Siswa dengan Buku IPAS Berbasis Media Visual di Kelas IV Madrasah Ibtidaiyah - Syabrina, Muhammad; Ma’rifah, Murni; Nortasya, Siti; Nisa, Widyu Nazzillah Khoirun (Moderasi : Journal of Islamic Studies, 2024)
Abstract Natural and Social Sciences (IPAS) subjects often pose challenges at the elementary school level due to the complexity and abstract nature of the material. Conventional textbooks are often inadequate in bridging the gap between student needs and understanding complex concepts. This study aims to analyze the effectiveness of using visual media-based science textbooks in improving the understanding of Grade IV students at MIS Fathul Iman Palangkaraya. The research employs a developmental approach, creating visual media-based textbooks that integrate illustrations, diagrams, and infographics relevant to IPAS materials. The implementation process was carried out over one semester, involving teachers and students as the primary subjects. Data were collected through observations, interviews, and student comprehension tests conducted before and after using the textbooks. The findings indicate that visual media-based textbooks significantly enhance students' interest and understanding of IPAS materials. Students became more engaged in the learning process, better connected abstract concepts to daily experiences, and demonstrated improved scores on comprehension tests. Teachers also acknowledged that this media facilitated more engaging and effective delivery of the materials.